2004
DOI: 10.1080/10635150490522610
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Morphological Evolution in Homobasidiomycetes Inferred Using Maximum Likelihood: A Comparison of Binary and Multistate Approaches

Abstract: The homobasidiomycetes is a diverse group of macrofungi that includes mushrooms, puffballs, coral fungi, and other forms. This study used maximum likelihood methods to determine if there are general trends (evolutionary tendencies) in the evolution of fruiting body forms in homobasidiomycetes, and to estimate the ancestral forms of the homobasidiomycetes and euagarics clade. Character evolution was modeled using a published 481-species phylogeny under two character-coding regimes: additive binary coding, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
81
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 43 publications
6
81
2
3
Order By: Relevance
“…The data show that fruitbody form and hymenophore type did not reflect phylogenetic relationships well. Later research has also confirmed this (Hibbett, 2004). Moncalvo et al (2000) investigated phylogenetic relationships within the order Agaricales with analysis of nuclear large subunit ribosomal DNA sequences.…”
Section: Advance Of Phylogenetic Systematics Of Agaricomycetes and Agmentioning
confidence: 85%
“…The data show that fruitbody form and hymenophore type did not reflect phylogenetic relationships well. Later research has also confirmed this (Hibbett, 2004). Moncalvo et al (2000) investigated phylogenetic relationships within the order Agaricales with analysis of nuclear large subunit ribosomal DNA sequences.…”
Section: Advance Of Phylogenetic Systematics Of Agaricomycetes and Agmentioning
confidence: 85%
“…It is evident, that sequestrization, the process that generate the gasteroid fruiting bodies, operates via the reduction or loss of certain structures, such as the stipe, the hymenium or forcible spore discharge (Hibbett 2004, Thiers 1984, Desjardin 2003, Binder et al 2005, Albee-Scott 2007. Thus, gasteroid forms have often been interpreted as reduced forms, although what reduction or simplification means on the cellular or biochemical level is obscure.…”
mentioning
confidence: 99%
“…One of the greatest challenges in fungal evolutionary biology is to explain how today's overwhelming diversity of fruiting body types evolved, and what processes and selective forces gave rise to the considerable morphological variability of fruiting body types of extant fungal species (Hibbett and Binder 2002;Desjardin 2003;Hibbett 2004;Binder et al 2005;Albee-Scott 2007). It has been suggested that many of the morphologies are highly adaptive and have evolved and continue to evolve in response to changes in environmental conditions (Peintner et al 2001;Albee-Scott 2007;Hibbett 2007).…”
mentioning
confidence: 99%
See 2 more Smart Citations